Crenças sobre o espanhol na escola pública : “bem-vindos ao mundo dos sonhos e das [im]possibilidades” - Vesz, Fernando Zolin (2012)
The purpose of this dissertation is to identify and comprehend the beliefs about the teaching and learning of Spanish as a foreign language in the public school. Eight participants (two parents, three students and three teachers) were interviewed, all of them from an elementary public school that has included Spanish as a foreign language in its syllabus since 2000. The qualitative interviews were based on King & Horrocks (2010) statements and generated accounts about the participants’ experience on teaching or learning Spanish as a foreign language in that school. In order to analyse the data, it was observed the social and discursive nature of beliefs, according to Kalaja (1995, 2003), Dufva (2003), Assis-Peterson, Cox & Góes dos Santos (2010) and Pan & Block (2011), which understands beliefs not only as personal points of view but also as echoes of predominant discourses that are social constructions. The research questions were the following: 1) what are the participants’ beliefs about the teaching and learning of Spanish as a foreign language in the public school?, and 2) what discourses may the set of beliefs be connected to? Results suggest that the teaching of Spanish as a foreign language in the public school seems to be discursively an artifice in order to maintain the social stratification and the status quo.